Skagway seen from the water, Alaska, ca. 1897. - La Roche, Frank (1892)
Caption on image: ""Skagway, Alaska"" To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number